The state of the art in cost-benefit of HTS methods for stock assessment: An overview - Rodríguez-Rodríguez, Gonzalo; Ballesteros, Hugo M.; Sánchez-Llamas, Eduardo; Bande, Roberto; Otero, Rosa Fernández (Frontiers in Marine Science, 2022)
Over the past two decades, enormous progresses have been made in High Throughput Sequencing (HTS) methods development. This fact unveiled the potential usefulness of HTS methods in a wide range of fields such as fisheries assessment and management, for which, their application has been extensively discussed. As a consequence of the rapid development, sequencing costs have continuously declined, leading to a general claim that HTS methods are cost-efficient compared with traditional ones. Within this context, the underlying research objective is to assess the cost-effectiveness of genomic techniques through a review of the State of Art (SoA) on three HTS methods: i) Environmental DNA (eDNA); ii) Epigenetics method for Age Determination through DNA methylation (DNAm), and; iii) Close-Kin Mark-Recapture (CKMR) applied on marine ecosystems and fisheries and for stock assessment purposes. The SoA review of the literature on HTS methods was performed through the Snow-balling systematic reviewing approach. The analysis has considered the set of processes and variables necessary to perform the stock assessment and compared the capacity of current and HTS methods for providing the required data. Research reveals that HTS methods constitute a promising tool for fisheries research, and, particularly, for improving scientific advice. Nevertheless, up to now only one research, on a non-commercial species, has been conducted on the application of HTS methods for stock assessment purposes. Even though some partial data are present in the literature, no systematic analysis on costs has been found. This paper suggests that the future research agenda should attempt to straddle both the scenarios for the transition process, considering complementary implementation and substitution possibilities and their cost-efficiency. Clarifying these questions is likely to pave the way for the effective and step-wise implementation of these methods in fisheries management, thus, further research is recommended to encompass the transition process.